Sociological aspects of political leadership at modern stage - Zuret Khalidovna Kobleva; Aminet Magametovna Siyukhova (Вестник Майкопского государственного технологического университета)
The article reveals the issues of sociology of leadership on the example of political leadership in modern Russian society. The need to consider the category of political leadership as a type of social institution has been grounded. The research methodology is based on the understanding of leadership as the ability of an individual to be the first to overcome stagnation in the life of social communities of different levels, leading the rest of the majority. The article reveals the essence of nominal and actual leadership, notes the significant role of the closest professional and personal environment of a leader, affirms that the influence of a nominal leader on the political situation is usually higher than the influence of so-called “grey cardinals”. The idea is emphasized that a political leader should not only indicate a goal and lead followers to it, but also form an idea of positive changes in the lives of specific people moving toward this goal. Professionalization as a high-quality academic and disciplinary training in humanitarian, economic and legal subjects is considered to be an important social basis for political leadership. The scientific novelty in the article is realized through the use of empirical material, reflecting the modern political realities of Russian political leadership.